Performance simulation of the integration of hybrid stand-alone photovoltaic system at Tuba Island - Shahril Irwan Sulaiman; Nur Amira Ali (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
Hybrid photovoltaic-diesel generator power system is important for rural electrification with the diesel generator supplying electricity when battery bank fails to meet the load demand. However, the operation of diesel generator could also be very costly due to high operation and maintenance cost when compared to photovoltaic-battery system. As a result, proper sizing must be conducted to determine the economic indicators of the hybrid photovoltaic-diesel generator system throughout its lifetime. This paper presents the design of such system for an island resort in Langkawi, Kedah, Malaysia. HOMER software was used to simulate the design parameters and economic performance of the system as compared to the existing diesel generator system. Apart from that, different capacities of PV array, battery bank and inverter were investigated in this study to determine the optimum configuration of these components such that the total cost of supplying the load demand at the resort could be minimized. The results showed that the hybrid photovoltaic-diesel generator system is more economically feasible than the existing diesel generator system used at the resort.